Community Education on Neonatal Visits: Reducing Risks, Enhancing Hope - Br Ginting Munthe, Novita; Sembiring, Iskandar Markus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The health of newborns is one of the key indicators of societal well-being. Neonatal visits play a crucial role in preventing health complications in infants. This article presents the outcomes of a community service program focused on educating the importance of neonatal visits. The community service activity was conducted at Mars Clinic, Deli Serdang Regency, North Sumatra, on November 29, 2024, involving 22 mothers of newborns. The primary goal of this community service initiative was to enhance the knowledge and awareness of the community regarding the significance of neonatal visits in preventing health risks in newborns. The activity was carried out using a participatory approach involving healthcare workers, community health volunteers, and the general public. A significant improvement was observed in the 'Good' category, increasing from 9.09% to 72.73%, alongside a drastic decrease in the 'Poor' category from 27.27% to 0%. The average increase in pre-test to post-test scores is 17.27 points, demonstrating the effectiveness of the educational methods implemented. The conclusion of this program underscores that community education can significantly reduce neonatal health risks and foster hope for a healthier generation.